Analisis Tingkat Kebisingan Pada Ruang Tunggu Penumpang Terminal Tirtonadi, Surakarta - Ahsan Risfathoni Almadani; Aini Mar'atush Sholekha; Berlian Warit Amalia; Muchammad Sholiqin; Siti Rachmawati (DPPM Universitas Pelita Bangsa, 2022)
The terminal is one of the public facilities in the field of transportation whose existence is not only beneficial for the community. Terminals can have a serious impact on the environment, one of which is noise. . Noise is a sound that is produced from an activity but is unwanted and can disturb humans. Tirtonadi Terminal is a type A bus terminal located in Surakarta City. The terminal waiting room is a gathering place for many people such as traders, passengers, bus officers and terminal officers. The purpose of this study was to obtain results that were relevant to those in the field and to identify efforts that could be used to reduce or prevent noise propagation from reaching residential areas. . This research data was taken by direct measurement technique and literature study. The data obtained are in the form of noise level data at each sample point, noise quality standards at the terminal, and data related to noise measurements. The noise level data obtained were analyzed quantitatively by using the Leq calculation formula. Based on the results of the analysis, it was found that the noise level value in the two waiting room areas at Tirtonadi Terminal was around 54.2 dBA. The noise value indicates that the noise level in the waiting room area of Tirtonadi Terminal does not exceed the noise level quality standard based on the Decree of the Minister of the Environment Number 48/MENLH/11/1996. Efforts that can be made to prevent noise include reducing the volume of sound produced, regulating vehicle operating times, limiting the number of bus operations, and using natural and artificial barriers. Keywords: Tirtonadi Terminal, Noise, Quality Standards